2004
DOI: 10.1167/iovs.04-0051
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inhibition of IL-1–Induced Collagen Degradation by Corneal Fibroblasts in Three-Dimensional Culture

Abstract: Dexamethasone exerted multiple effects on the MMP-TIMP system in corneal fibroblasts and thereby inhibited IL-1beta-induced collagen degradation by these cells. Inhibition of the IL-1beta-induced activation of ERK and JNK may contribute to these effects of dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
2
41
0
6
Order By: Relevance
“…We have previously shown that dexamethasone and female sex hormones as well as ATRA also inhibit collagen degradation by corneal fibroblasts likely through suppression of MMP expression. 14,16,17,21 These data thus suggest that RAR-c signaling modulates the expression of MMPs in corneal fibroblasts and thereby contributes to the regulation of collagen remodeling in the corneal stroma both under physiological conditions and during the development of pathologic conditions such as corneal infection, scar formation, and inflammation. Indeed, we have recently found that topical application of ATRA ameliorates corneal ulceration induced by injection of bacterial lipopolysaccharide into the corneal stroma of rabbits.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have previously shown that dexamethasone and female sex hormones as well as ATRA also inhibit collagen degradation by corneal fibroblasts likely through suppression of MMP expression. 14,16,17,21 These data thus suggest that RAR-c signaling modulates the expression of MMPs in corneal fibroblasts and thereby contributes to the regulation of collagen remodeling in the corneal stroma both under physiological conditions and during the development of pathologic conditions such as corneal infection, scar formation, and inflammation. Indeed, we have recently found that topical application of ATRA ameliorates corneal ulceration induced by injection of bacterial lipopolysaccharide into the corneal stroma of rabbits.…”
Section: Discussionmentioning
confidence: 84%
“…We have previously shown that the amounts of pro or active forms of MMP-1, MMP-2, MMP-3, and MMP-9 in such culture supernatants are increased by exposure of the cells to IL-1b 14 and that these effects are inhibited by ATRA. 17 Immunoblot analysis and gelatin zymography revealed that the amount of ProMMP-1, active MMP-1, ProMMP-2, active MMP-2, ProMMP-3, active MMP-3, ProMMP-9, and active MMP-9 in the supernatants from cultured cells were increased by IL-1b.…”
Section: Effects Of R667 On Mmp Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 After corneal injury, IL-1 protein is detectable in corneal fibroblasts. IL-1 up-regulates the expression of various cytokines or enzymes by corneal fibroblasts, 8,22,39 and it also contributes to wound healing. In our model, IL-1␤ binds to the IL-1 receptor on corneal fibroblasts, up-regulates various angiogenesis-related factors, and induces corneal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…20 NF-B plays an important role in IL-1␤-related inflammatory diseases, including various corneal diseases. 21,22 Blockade of NF-B reduces corneal epithelial defects during healing in a model of corneal injury. 21 However, it is unknown whether dexamethasone has an impact on IL-1␤-dependent angiogenesis.…”
mentioning
confidence: 99%